DIHYDROTESTOSTERONE DOWNREGULATES BONE RESORPTION ACTIVITY OF OSTEOCLASTS IN DOSE DEPENDENT MANNER: AN IN VITRO MODEL USING RAW 264.7 CELLS - Thu, Hnin Ei; Hussain, Zahid; Mohamed, Isa Naina; Shuid, Ahmad Nazrun (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: Numerous studies have evidenced the bone regulatory potential of dihydrotestosterone in androgen-deficient osteoporosis. The present study was thus aimed to explore the translational mechanism of dihydrotestosterone to down-regulate the bone resorption activity of osteoclasts using RAW 264.7 cells as in vitro model. Methods: Prior to analyze the efficacy of dihydrotestosterone (5Î±-DHT) to alleviate osteoclastic differentiation, their cell viability and cell proliferative ability was assessed using lactate dehydrogenase (LDH) and MTS assays. The osteoclastic differentiation capacity of dihydrotestosterone was evaluated by measuring TRAP activity and the expression of bone resorption-related proteins such as matrix metallopeptidase-9 (MMP-9), cathepsin-K, tartrate-resistant acid phosphatase (TRAP) and NFATc1. Moreover, the effects of dihydrotestosterone were also evaluated on superoxide (free radicals) generation and superoxide dismutase (SOD) activity in RANKL-induced osteoclasts. Results: Dihydrotestosterone showed no toxicity towards RAW 264.7 cells and significantly enhanced their proliferation and growth rates in a dose-dependent fashion. It was also observed that dihydrotestosterone exhibits a remarkable inhibitory effect on differentiation, maturation and activation of osteoclasts. The marked inhibition of differentiation and activation of osteoclasts caused by 5Î±-DHT was due to down-regulation of the expression of MMP-9, cathepsin-K, TRAP, NFATc1, generation of superoxide and up-regulation of SOD activity in the RAW 264.7 cells. Conclusion: Resulting data provided substantially in vitroevidence for the pronounced anti-osteoclastogenetic activity of dihydrotestosterone and its therapeutic value in treating osteoporosis and other bone-erosive disorders. Â 